2021
DOI: 10.1186/s12879-021-06644-0
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the uptake of continuous care among people living with HIV receiving antiretroviral therapy and social determinants of the uptake of continuous care in the southwest of China: a cross-sectional study

Abstract: Background Continuous care is essential for people living with HIV. This study aimed to measure continuous care uptake and investigate the association between higher uptake of continuous care and behavioral and social factors, including HIV-acquisition risk and socioeconomic characteristics. Methods A hospital-based cross-sectional study was conducted from April to November 2019 in an HIV treatment center of a specialized hospital in Kunming city, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
1
0
1
Order By: Relevance
“…Generally, a person whose high education would tend to utilize health services as well as possible (Saracino et al, 2018). Education level was a significant factor in visiting health services continuously among PLHIV in China (Jin et al, 2021). A study in Africa found higher education levels increased the accessibility to following ARV therapy (Erena et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, a person whose high education would tend to utilize health services as well as possible (Saracino et al, 2018). Education level was a significant factor in visiting health services continuously among PLHIV in China (Jin et al, 2021). A study in Africa found higher education levels increased the accessibility to following ARV therapy (Erena et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Estudiar los ítems de apoyo social y familiar implica hablar de redes sociales y de los intercambios y flujos relacionales, emocionales y materiales que en estas se efectúan. A más fragilidad de estas redes menos posibilidades de soporte y sostén (Erten et al, 2022;Jin et al, 2021;Kim et al, 2021).…”
Section: Discussionunclassified